Barbie : Fairytopia - Universal Studios Home Entertainment (Firm); Mattel Entertainment (Firm); Mainframe Entertainment (Firm) (Universal City, CA Universal Studios Home Entertainment, 2011)
Just through the rainbow, in the world of Fairytopia, lives Elina, a beautiful flower fairy who longs to have wings. Her home is a large flower in the Magic Meadow where she lives with Bibble, a quirky but lovable puffball. One day Elina wakes to find that her flower home is sick, and that her fairy friends can't fly! She summons the courage to help and embarks on a fantastic journey to find Azura, a Guardian Fairy she thinks can solve the problem.
Animated.
Includes music video.
Voices: Kelly Sheridan, Lee Tockar, Tabitha St. Germain, Kathleen Barr, Venus Terzo.
Not rated.
DVD; anamorphic widescreen; Dolby Digital 5.1 surround (English), 2.0 stereo (English, French, Spanish).
English, French or Spanish dialogue.
Keywords: Barbie -- (Fictitious character) -- Juvenile films; Spanish language -- Bilingual; French language -- Bilingual; Fairies -- Juvenile films; Fairy plays; Animated films; Children's films; Drama; Feature films; Fiction films; Juvenile works; Video recordings for the hearing impaired